2020
DOI: 10.1111/pce.13723
|View full text |Cite|
|
Sign up to set email alerts
|

Silencing of OsCV (chloroplast vesiculation) maintained photorespiration and N assimilation in rice plants grown under elevated CO2

Abstract: High CO2 concentrations stimulate net photosynthesis by increasing CO2 substrate availability for Rubisco, simultaneously suppressing photorespiration. Previously, we reported that silencing the chloroplast vesiculation (cv) gene in rice increased source fitness, through the maintenance of chloroplast stability and the expression of photorespiration‐associated genes. Because high atmospheric CO2 conditions diminished photorespiration, we tested whether CV silencing might be a viable strategy to improve the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 63 publications
0
24
0
Order By: Relevance
“…37,38 Previous studies in Arabidopsis and rice have reported that AtCV silencing is a potent strategy that enhances plant tolerance to water deficit by maintaining chloroplast integrity. 38,39 Furthermore, the expression of OsCV-related genes was increased in rice under drought conditions. 38 OsCV acts as a scaffold for binding to peroxisomal proteins and plays a role in the marketing of chloroplast proteins.…”
Section: •−mentioning
confidence: 99%
See 1 more Smart Citation
“…37,38 Previous studies in Arabidopsis and rice have reported that AtCV silencing is a potent strategy that enhances plant tolerance to water deficit by maintaining chloroplast integrity. 38,39 Furthermore, the expression of OsCV-related genes was increased in rice under drought conditions. 38 OsCV acts as a scaffold for binding to peroxisomal proteins and plays a role in the marketing of chloroplast proteins.…”
Section: •−mentioning
confidence: 99%
“…38 OsCV acts as a scaffold for binding to peroxisomal proteins and plays a role in the marketing of chloroplast proteins. 39 The aims of this study were to elucidate the molecular mechanism underlying MT-mediated leaf senescence in tomato. We obtained SlM3H-overexpressing (OE) transgenic tomato plants to investigate the role of endogenous MT in regulating tomato leaf senescence and identified the downstream target gene SlCV of MT involved in ROS homeostasis.…”
Section: •−mentioning
confidence: 99%
“…SAVs are small protein lytic compartments containing chloroplast stroma-targeted fluorescent proteins that can be transported to vacuoles for degradation [ 15 ]. Chloroplast vesiculation, a new type of chloroplast degradation pathway, is independent of SAVs and autophagy and has been demonstrated to be involved in the degradation of chloroplast thylakoid-associated proteins [ 14 , 16 ]. There are three types of chloroplast component degradation via the autophagy pathway: the rubisco-containing body (RCB) [ 4 ], the Autophagy-related 8—interacting protein 1—green fluorescent protein labels plastid-associated body (ATI-PS body) [ 17 ], and small starch granule-like structures (SSGL) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Zhou et al (2020) showed that tomato plants grown at elevated CO 2 concentration were more sensitive to combined drought and heat stress than those grown at ambient CO 2 due to a higher decrease in net photosynthesis, stomatal conductance, and transpiration, leading to an increased severity of the waterdeficit effects. Although, in general, high CO 2 levels promote vegetative growth due to increased CO 2 fixation, altered redox state, reduced photorespiration, and improved WUE, the effects of high CO 2 concentrations on grain quality, and particularly grain protein content could be negative if N availability is limited (e.g., Umnajkitikorn et al, 2020). This is another aspect of high CO 2 and stress combination that needs to be addressed, particularly in light of the potential negative effects of stress combinations on NUE.…”
Section: Stress Combination In a High Co 2 Environmentmentioning
confidence: 99%